Potential of Liposomal FTY720 for Bone Regeneration: Proliferative, Osteoinductive, Chemoattractive, and Angiogenic Properties Compared to Free Bioactive Lipid - Mouzoura P; Marazioti A; Gkartziou F; Metsiou DN; Antimisiaris SG (International Journal of Nanomedicine)
Panagiota Mouzoura,1 Antonia Marazioti,1,2 Foteini Gkartziou,1 Despoina-Nektaria Metsiou,1 Sophia G Antimisiaris1,3 1Pharmaceutical Technology Laboratory, Department of Pharmacy, University of Patras, Rion, 26504, Greece; 2Laboratory of Basic Sciences, Department of Physiotherapy, University of the Peloponnese, Sparti, 23100, Greece; 3FORTH/ICE‑&EEgr;&Tgr;, Institute of Chemical Engineering Sciences, Platani, 26504, GreeceCorrespondence: Sophia G Antimisiaris, Laboratory of Pharm Technology, University of Patras, Pharmacy Building, Rio Campus, Rio Patras, 26504, Greece, Tel +30-2610-962332, Email santimis@upatras.grIntroduction: FTY720 bioactive lipid has proliferative, osteoinductive, chemo attractive, and angiogenic properties, being thus a potential exogenous administered agent for promotion of bone regeneration. Herein we developed FTY720-loaded liposomes as a potential delivery system that could retain and prolong the bioactivity of the bioactive lipid and at the same time reduce its cytotoxicity (at high doses).Methods: FTY720 liposomes were prepared by thin-lipid hydration and microfluidic flow focusing, and evaluated for their ability to induce proliferation, osteoinduction, and chemoattraction in three cell types: MC3T3-E1 pre-osteoblast cells, L929 fibroblast cells, and ATDC5 chondrogenic cells. The angiogenic activity of free and liposomal FTY720 was investigated using a chick chorioallantoic membrane assay. NBD-FTY720 cellular uptake was quantitated using flow cytometry and morphologically assessed by confocal microscopy. Implicated cellular signaling mechanisms were investigated by quantifying phosphorylated MAPK and CREB proteins.Results: FTY720 liposomes (~80– 110 nm) with low polydispersity and ~100% loading were prepared using both methods. FTY720 demonstrated the ability to increase cell proliferation at 10– 300nM doses but was cytotoxic at doses> 400nM while the corresponding liposomal-FTY720 doses were non-cytotoxic, proving its reduced toxicity. In several cases (cells and doses), FTY720 liposomes demonstrated increased osteogenic differentiation of cells, proliferation, and migration compared to free FTY720, whereas both FTY720 forms demonstrated substantial angiogenic activity. Liposomal FTY720 cellular uptake was substantially higher than that of free FTY720 in some cases, a fact that may be connected to its higher bioactivity. Increased phosphorylated MAPK and CREB protein concentrations provided information about the potential cellular signaling mechanisms involved in FTY720-induced osteogenesis.Discussion: The current results confirm the high potential of FTY720 bioactive lipid, especially in its liposomal form, that demonstrated substantial reduction of cytotoxicity and prolonged preservation of the lipids bioactivity (compared to the free lipid), for accelerated treatment of bone defects. Interestingly, the current studies prove the potential of FTY720, especially in its liposomal form, to promote reprogramming of L929 fibroblasts into osteoblasts, a novel finding deserving future exploitation. Keywords: microfluidics, bioactive lipid, osteogenesis, re-programming, mineralization, chemotaxis, proliferation, MC3T3-E1, L929, ATDC5